2005
DOI: 10.1159/000090099
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Prosody in Interaction Control

Abstract: This paper investigates prosodic aspects of turn-taking in conversation with aview to improving the efficiency of identifying relevant places at which a machinecan legitimately begin to talk to a human interlocutor. It examines the relationshipbetween interaction control, the communicative function of which is to regulatethe flow of information between interlocutors, and its phonetic manifestation.Specifically, the listener’s perception of such interaction control phenomena ismodelled. Algorithms for automatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 15 publications
3
50
0
Order By: Relevance
“…Swedish has two basic intonation patterns, medial fall (H*L%) and fall-rise (H*LH%) (Bruce, 1977). Thus, in an analysis of the prosodic aspects of turn-taking in Swedish, Edlund & Heldner (2005) makes a distinction between patterns with a final rise and a final fall. This analysis shows that a rising intonation was followed by an equal distribution of speaker 4 changes and speaker holds (51% and 49% respectively), implying that the turn-taking effects of a rising intonation in Swedish are unclear.…”
Section: Turn-taking Cuesmentioning
confidence: 99%
“…Swedish has two basic intonation patterns, medial fall (H*L%) and fall-rise (H*LH%) (Bruce, 1977). Thus, in an analysis of the prosodic aspects of turn-taking in Swedish, Edlund & Heldner (2005) makes a distinction between patterns with a final rise and a final fall. This analysis shows that a rising intonation was followed by an equal distribution of speaker 4 changes and speaker holds (51% and 49% respectively), implying that the turn-taking effects of a rising intonation in Swedish are unclear.…”
Section: Turn-taking Cuesmentioning
confidence: 99%
“…However, spontaneous conversational speech frequently contains silent pauses inside what we would intuitively group into turns, complete utterances, or sentence-like units, and inside what are indeed semantically coherent units, and dialog systems using silence-based endpoint detection run into problems with unfinished utterances when encountering spontaneous speech [2]. Experiments presented in [11] showed that dialog systems relying on silence-based segmentation run the risk of interrupting their users in as much as 35% of all silent pauses in the kind of speech investigated.…”
Section: Silence Duration Thresholdsmentioning
confidence: 99%
“…In [11] it was shown that the number of incorrect turn-taking decisions can be reduced substantially by combining standard silence-based endpoint detection with an automatic classification of intonation patterns. In the process, it is also possible to decrease the length of the required silence without any loss in performance.…”
Section: /Nailon/ -Online Automatic Extraction Of Prosodic Cuesmentioning
confidence: 99%
“…Methods involving both syntactic and semantic completeness (e.g. [6]) as well as prosody [10] have been shown to improve the situation, and we are currently investigating their use in HIGGINS.…”
Section: Interaction Controlmentioning
confidence: 99%